A48: Durometer Measures Discriminate Affected versus Normal Skin in Pediatric Localized Scleroderma. Issue 11 (March 2014) - Poff, Sarah; Li, Suzanne C.; Kelsey, Christina; Foeldvari, Ivan; Torok, Kathryn S.
Abstract : Background/Purpose: Localized scleroderma (LS) is an autoimmune, inflammatory disease of the skin and subdermal tissues, resulting in fibrosis and atrophy. Outcomes are monitored by scoring signs of inflammation and damage to compose the LS cutaneous assessment tool (LoSCAT). The utility of skin scoring is limited by the need for training and ongoing practice and its inherent subjectiveness. Establishing an objective, simple, measure of skin disease would facilitate standardized outcomes for multicenter studies. One component of the LoSCAT is skin thickness (ST), graded by the clinician using the Rodnan Skin Score (0–3 ST). A surrogate for ST is skin hardness, which can be measured by a tool called a durometer, in durometer units. Among adults with systemic sclerosis, the durometer is a valid measure of skin hardness with high intra– and inter–rater reliability, correlation to skin scores, and sensitivity to change over time. This study was undertaken to examine the validity of the durometer as a measure of disease in pediatric LS. Methods: Patients from two separate clinics who attended regular appointments for LS were eligible to participate. After consent, durometer measures were taken of a single LS lesion, the "study lesion, " as well as an area of normal skin, typically in a contralateral location. Measures were taken in triplicate on either edge of the study lesion and normal skin and at approximately 1cm intervals from edge to edge. Durometer readings were repeated at up to 5 follow–up visits. The highest durometer reading from the study lesion and corresponding normal skin at each patient's initial visit was used for statistical analysis. Affected and unaffected skin was compared using a paired sample t–test. At each visit concurrent standardized clinic outcome measures were obtained, including the LoSCAT. Results: Seventeen patients were included in the analysis; most were female (76%) and Caucasian (88%) with a linear subtype of LS (41%). Mean age was 13.5 yrs old during the study and 9.0 yrs old at the onset of disease. Seven patients had study lesions on the chest or back, 2 on the abdomen, and 8 on the limbs. Analysis revealed a significant difference between durometer measures of affected and unaffected skin with a p–value of <0.001. The median durometer reading was 40 (IQR: 25–48) for study lesions and 19.5 (IQR: 12.75–29) for normal skin. An upward trend was seen for durometer measures of study lesions with increasing ST scores (see figure) Conclusion: Among pediatric patients with LS the durometer serves as an objective measure of skin hardness, discriminating affected versus unaffected skin on the trunk and limbs. This tool may serve as a surrogate for ST, though further analysis is needed to examine its sensitivity to change over time. A larger study would be helpful to further correlate durometer ranges with ST scores.